1990
DOI: 10.1016/0014-5793(90)80073-r
|View full text |Cite
|
Sign up to set email alerts
|

Potassium chemotaxis in Rhodobacter sphaeroides

Abstract: The addition of potassium to Rhodobacter sphaeroides in the absence of magnesium increased the membrane potential, as measured by the carotenoid bandshift. In the presence of magnesium, potassium decreased the membrane potential. Potassium stimulated the mean population swimming speed by 33% and 48% in the presence or absence of magnesium, respectively. Chemotactic responses of R. sphaeroides to potassium were also unaffected by the presence or absence of magnesium. These results suggest that the membrane pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Membrane-spanning chemoreceptors (methyl-accepting chemotaxis proteins) (1,8) have not been found (3,17), and all identified chemoattractants are also metabolites (4,9). We have shown that attractants must be transported into the cell for a response to occur, but we had not conclusively identified whether the energetic process of transport caused the chemotactic signal or whether subsequent metabolism of the effector was required (9,12,13).…”
mentioning
confidence: 93%
“…Membrane-spanning chemoreceptors (methyl-accepting chemotaxis proteins) (1,8) have not been found (3,17), and all identified chemoattractants are also metabolites (4,9). We have shown that attractants must be transported into the cell for a response to occur, but we had not conclusively identified whether the energetic process of transport caused the chemotactic signal or whether subsequent metabolism of the effector was required (9,12,13).…”
mentioning
confidence: 93%
“…In the presence of the carbon source succinate there was no significant change in the speed at which the ceils swam after phosphate addition, in fact 0.1 mM caused an increase. Potassium is known to increase the swimming speed of R. sphaeroides [8], and indeed potassium phosphate had little effect on the swimming speed of R. sphaeroides, presumably because the potassium antagonised the effect of phosphate (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…It lacks the methyl accepting chemotaxis proteins found in the enteric bacteria and has consequently been studied as a model system of receptor independent chemotaxis [2][3][4][5][6][7]. Many chemoattractants, such as the organic acids and potassium cause an increase in the mean swimming speed and a decrease in the stopping frequency [4,8]. Further analysis of these effects suggests some compounds have two different effects on the flagellar motor of R. sphaeroides.First, there is a true chemotactic response, and secondly, some compounds cause an additional excitation of motility [6].…”
mentioning
confidence: 99%
“…shows chemokinesis, by the addition of certain chemoeffectors e.g. organic acids [12]. As *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%